Change in Atlantic cod migrations and adaptability of early land-based fishers to severe climate variation in the North Atlantic. (July 2022) - Edvardsson, Ragnar; Patterson, William P.; Bárðarson, Hlynur; Timsic, Sandra; Ólafsdóttir, Guðbjörg Ásta
ABSTRACT: We use biochemical, biological, archaeological, and historical analysis to examine relationships between Atlantic cod migration, sea temperature, and shifts in the distribution and occupancy of historical fishing sites in Iceland during the last millennium. Results support the hypothesis that the cooling climate of the North Atlantic during the period commonly referred to as the Little Ice Age coincided with changes in Atlantic cod migration patterns. Historical analysis shows a concomitant increase in reports of worsening Atlantic cod fishing and a severe decrease in domestic fishing, particularly in north Iceland. We conclude that Atlantic cod fisheries in Iceland originally thrived because of the proximity to cod migration routes. However, despite the mobility of local fishers, fluctuations in fish migrations, coupled with a harsher climate and increased competition for fishing grounds, resulted in a stagnation that lasted until the eventual modernization of the fishery in the mid-nineteenth century.